Body Searches and Imprisonment - Daems, Tom (Palgrave Studies in Prisons and Penology, 2023)
Chapter 1. Body searches as contested control measures -- Chapter 2. The imposition of power through touch: A sensory criminology approach to understanding body searches -- Chapter 3. Searching, ‘state of security’ and the structuration of prison security -- Chapter 4. Strip searches: A risky practice that needs to be monitored -- Chapter 5. Strip searches through the lens of the prohibition of inhuman and degrading treatment in European human rights law -- Chapter 6. Body searches and vulnerable groups: Women and LGBTQI+ people in prison -- Chapter 7. Body searches in Belgian prisons: dignity, security and denial -- Chapter 8. Body searches in French prisons: Dignity and security on a roller coaster -- Chapter 9. Stripping the self away: security, control, and punishment in the practice of strip searches in Spanish prisons -- Chapter 10. Gendered punishment and protest in a context of conflict: Strip searching in Northern Ireland -- Chapter 11. “There’s a tech for that”: balancing dignity and security in carceral settings through alternative technology devices -- Chapter 12. What future for body searches in prisons?.